Electrochemical oxidative degradation of X-6G dye by boron-doped diamond anodes: Effect of operating parameters. (November 2020) - Tang, Yining; He, Deliang; Guo, Yanni; Qu, Wei; Shang, Jun; Zhou, Lei; Pan, Rong; Dong, Wei
Abstract: Boron-doped diamond (BDD) is an excellent electrode material. As the anode in an electrochemical degradation tank, BDD has been receiving widespread attention for the treatment of azo dye wastewater. In this study, electrochemical oxidation (EO) was applied to electrolyze reactive brilliant yellow X-6G (X-6G) using BDD as the anode and Pt as the cathode. To balance the degradative effects and power consumption in the electrolysis process, the effects of a series of operating parameters, including current density, supporting electrolyte, initial pH, reaction temperature and initial dye concentration, were systematically studied. The oxidative process was analyzed by color removal rate, and the degree of mineralization was evaluated by TOC. The optimal experimental parameters were finally determined: 100 mA cm −2, 0.05 M Na2 SO4 electrolyte, pH 3.03, 60 °C, and an initial X-6G concentration of 100 mg L −1 . As a result, color completely disappeared after 0.75 h of electrolysis, and TOC was removed by 72.8% after 2 h of electrolysis. In conclusion, the EO of a BDD electrode as an anode can be a potent treatment method for X-6G synthetic wastewater. Graphical abstract: Image 1 Highlights: BDD electrodes have advantages for the electrochemical degradation of X-6G. Current density, temperature, and pH have a great effect on the X-6G degradation. The X-6G can be completely decolored even at low current density. Low energy consumption and high mineralization rate (TOC = 73.8%).